PENGARUH KONSENTRASI SUKROSA TERHADAP KUALITAS FISIK DAN KADAR ANTIOKSIDAN NATA DE DRAGON - Anis Usfah Prastujati; Mustofa Hilmi; Asmaul Khusna; Ninik Sri Rahayu Wilujeng (Program Studi Agribisnis Fakultas Pertanian, 2023)
The harvest of dragon fruit in Banyuwangi Regency often makes the availability of dragon fruit very abundant so that the selling price is so low that dragon fruit farmers throw it away and make dragon fruit as animal feed, compost, and even throw it into the river as a form of their disappointment with this condition. In terms of nutritional components, dragon fruit has a high antioxidant content, which is useful for counteracting free radicals in the body. The benefits of the dragon fruit become useless when the main harvest arrives and the amount of dragon fruit is very large. Through this research, researchers want to make dragon fruit into processed food that has added value, namely nutritional value and high economic value, one of which is by making dragon fruit into nata de dragon as an alternative to functional food because it is made using starter culture from acetic acid bacteria. Namely, Acetobacter xylinum which can form glucose bonds to become extracellular cellulose (fiber) which is beneficial for the health of the body through the digestive tract. This research was conducted at the Food Processing Laboratory, Study Program D-IV Livestock Product Processing Technology, Banyuwangi State Polytechnic with 3 treatments of sucrose concentrations, namely 4, 6, and 8%. The results of ANOVA showed that the sucrose concentration significantly affected on the antioxidant levels of nata de dragon.